Antimalarial Drug Resistance: A Brief History of Its Spread in Indonesia - Fitri LE; Pawestri AR; Winaris N; Endharti AT; Khotimah ARH; Abidah HY; Huwae JTR (Dove Medical Press, 2023)
Loeki Enggar Fitri,1,2 Aulia Rahmi Pawestri,1,2 Nuning Winaris,1,2 Agustina Tri Endharti,1 Alif Raudhah Husnul Khotimah,3,4 Hafshah Yasmina Abidah,3,4 John Thomas Rayhan Huwae3,5 1Department of Parasitology Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 2AIDS, Toxoplasma, Opportunistic Disease and Malaria Research Group, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 3Master Program in Biomedical Science, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 4Medical Doctor Profession Education, Faculty of Medical and Health Science, Maulana Malik Ibrahim State Islamic University, Malang, Indonesia; 5Medical Doctor Profession Study Program Faculty of Medicine, Universitas Brawijaya, Malang, IndonesiaCorrespondence: Alif Raudhah Husnul Khotimah, Master Program in Biomedical Science, Faculty of Medicine, Universitas Brawijaya, 65145, District Lowokwaru, Malang, East Java, Indonesia, Tel +62 822 573 458 27, Fax +62 341 564755, Email husnulk556@gmail.com; alifraudhah_hk@student.ub.ac.idAbstract: Malaria remains to be a national and global challenge and priority, as stated in the strategic plan of the Indonesian Ministry of Health and Sustainable Development Goals. In Indonesia, it is targeted that malaria elimination can be achieved by 2030. Unfortunately, the development and spread of antimalarial resistance inflicts a significant risk to the national malaria control programs which can lead to increased malaria morbidity and mortality. In Indonesia, resistance to widely used antimalarial drugs has been reported in two human species, Plasmodium falciparum and Plasmodium vivax. With the exception of artemisinin, resistance has surfaced towards all classes of antimalarial drugs. Initially, chloroquine, sulfadoxine-pyrimethamine, and primaquine were the most widely used antimalarial drugs. Regrettably, improper use has supported the robust spread of their resistance. Chloroquine resistance was first reported in 1974, while sulfadoxine-pyrimethamine emerged in 1979. Twenty years later, most provinces had declared treatment failures of both drugs. Molecular epidemiology suggested that variations in pfmdr1 and pfcrt genes were associated with chloroquine resistance, while dhfr and dhps genes were correlated with sulfadoxine-pyrimethamine resistance. Additionally, G453W, V454C and E455K of pfk13 genes appeared to be early warning sign to artemisinin resistance. Here, we reported mechanisms of antimalarial drugs and their development of resistance. This insight could provide awareness toward designing future treatment guidelines and control programs in Indonesia.Graphical Abstract: Keywords: Indonesia, antimalarial resistance, chloroquine, sulfadoxine-pyrimethamine, primaquine, artemisinin